2005
DOI: 10.1073/pnas.0504039102
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis TCP20 links regulation of growth and cell division control pathways

Abstract: During postembryonic plant development, cell division is coupled to cell growth. There is a stringent requirement to couple these processes in shoot and root meristems. As cells pass through meristems, they transit through zones with high rates of cell growth and proliferation during organogenesis. This transition implies a need for coordinate regulation of genes underpinning these two fundamental cell functions. Here, we report a mechanism for coregulation of cell division control genes and cell growth effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
287
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 305 publications
(303 citation statements)
references
References 48 publications
9
287
0
4
Order By: Relevance
“…The distribution of molecular markers for the G2-to-M transition, CycB1;1 DB :GUS or CycB1;1 DB :GFP, has been used as a marker for the PD of the RAM (Colon-Carmona et al, 1999;Hauser and Bauer, 2000;Aida et al, 2004;Ticconi et al, 2004;Li et al, 2005;Cruz-Ramırez et al, 2012).…”
Section: The Growing Part Of the Root Consists Of Three Discrete Regionsmentioning
confidence: 99%
“…The distribution of molecular markers for the G2-to-M transition, CycB1;1 DB :GUS or CycB1;1 DB :GFP, has been used as a marker for the PD of the RAM (Colon-Carmona et al, 1999;Hauser and Bauer, 2000;Aida et al, 2004;Ticconi et al, 2004;Li et al, 2005;Cruz-Ramırez et al, 2012).…”
Section: The Growing Part Of the Root Consists Of Three Discrete Regionsmentioning
confidence: 99%
“…I propose a model in which there are two separate cell-cycle arrest fronts progressing from the tip to the base during leaf development: a primary front that determines arrest of general cell division in the primordium, followed by a secondary front that involves PPD and arrests DMC proliferation. The shape and progression of the primary arrest front is known to be influenced by class II TCP genes, CIN in Antirrhinium (19) or TCP2 and TCP4 in Arabidopsis (20), and it has been suggested that the extent of cell proliferation in the primordium may be regulated by a balance between the antagonistic activities of class I and II TCP genes on the expression of cyclin and ribosomal protein genes (28). Other genes, such as ANT, ARGOS, AN3, GRF5, JAG, SMP, and SWP, which promote cell division during leaf development, also seem to act on proliferation in the primordium (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…TB1 is expressed in organs that are suppressed in both maize and teosinte (Hubbard et al, 2002). In maize, there is an increase in the expression of TB1 relative to teosinte, causing buds to be suppressed, perhaps by affecting the cell cycle (Kosugi and Ohashi, 1997;Hubbard et al, 2002;Li et al, 2005). The increase in expression is proposed to be due to selection at a distant enhancer upstream of the TB1 locus (Clark et al, 2004(Clark et al, , 2006.…”
Section: Role Of Tb1 In Integration Of Responses To Hormones and Thementioning
confidence: 99%